A molecular mechanism for how sigma factor AlgT and transcriptional regulator AmrZ inhibit twitching motility in Pseudomonas aeruginosa. (24th March 2020) - Xu, Anming; Zhang, Miaokun; Du, Weili; Wang, Di; Ma, Luyan Z.
Summary: Pseudomonas aeruginosa isolates from cystic fibrosis patients are often mucoid (due to the overexpression of exopolysaccharide alginate) yet lost motility. It remains unclear about how P. aeruginosa coordinately regulates alginate production and the type IV pili‐driven twitching motility. Here we showed that sigma 22 factor (AlgT/U), an activator of alginate biosynthesis, repressed twitching motility by inhibiting the expression of pilin (PilA) through the intermediate transcriptional regulator AmrZ, which directly bound to the promoter region of pilA in both mucoid strain FRD1 and non‐mucoid strain PAO1. Four conserved AmrZ‐binding sites were found in pilA promoters among 10 P. aeruginosa strains although their entire pilA promoters had low identity. AmrZ has been reported to be essential for twitching in PAO1. We found that AmrZ was also required for twitching in mucoid FRD1, yet a high level of AmrZ inhibited twitching motility. This result was consistent with the phenomenon that twitching is frequently repressed in mucoid strains, in which the expression of AmrZ was highly activated by AlgT. Additionally, AlgT also inhibited the transcription of pilMNOP operon, which is involved in efficient pilus assembly. Our data elucidated a mechanism for how AlgT and AmrZ coordinately controlled twitching motility in P. aeruginosa .